Effect of bioregulators on spore germination of Mycovellosiella phaseoli, a floury leaf spot pathogen of Frenchbean - and B.M. SINGH, K.D. SHARMA, R.P. KAUSHAL (Indian Phytopathology, 2002)
Germination of spores of M. phaseoli was stimulated by all sugars and vitamins tested, and except for histidine and glutathione, it was stimulated by all amino acids. Benzylamino purine (BAP) [benzyladenine], abscisic acid and IAA were inhibitory tospore germination. The optimum temperature for germination was 20deg C.